Trends in Wrist Arthroscopy - Obdeijn, Miryam C.; Tuijthof, Gabrielle J. M.; van der Horst, Chantal M. A. M.; Mathoulin, Christophe; Liverneaux, Philippe (Journal of Wrist Surgery, 2013)
Background Wrist arthroscopy plays a role in both the diagnosis and the treatment of wrist pathology. It has evolved in the last three decades.Questions The present status of wrist arthroscopy was investigated by answering the following questions:-What is its current position in the treatment wrist pathologies according to the literature?-What is its current position according to hand surgeons?Methods Analysis of the number of publications on wrist arthroscopy was performed and compared with the number of publications on other arthroscopy topics to assess the current position of wrist arthroscopy. The members of the EWAS (European Wrist Arthroscopy Society) and the members of eight national hand surgery societies were questioned on wrist arthroscopy in daily practice.Results From 1975 till now, 925 papers on wrist arthroscopy were found. The publications on wrist arthroscopy increased from an average of 8/year (1986) to 26/year (2012). More than half (56.9%) of the respondents of the EWAS perform fewer than 5 wrist arthroscopies per month, and only 7 (10.8%) indicate the performance of more than 10 wrist arthroscopies per month. Seventy-four percent of the orthopedic hand surgeons perform wrist arthroscopy (in 48.5% for therapeutic indications) against 36.8% of plastic surgery hand surgeons (in 23.1% for therapeutic indications).Conclusion Wrist arthroscopy has taken up a place in the armamentarium of the hand surgeon. The place of wrist arthroscopy in daily practice is related to the background of the hand surgeon.
Keywords: indications; survey; wrist arthroscopy; hand surgeons